Utilization of Marble Waste and Ceramic Waste as Partial Replacement of Fine and Coarse Aggregate in Manufacturing of Concrete to be Used for Rigid Pavement (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is a widely used and versatile  building material worldwide. Its appealing characteristics,  such as elevated resistance to compression and favourable malleability, consistently allure constructors for its cost effective usage as a building material. Rising population  and technological progress in the manufacturing industry  have resulted in the extensive usage of consumer goods,  thereby posing challenges in managing the waste generated,  particularly for non-decomposable materials. In this study work parameters chosen as variable was marble and  ceramic waste. The compressive and flexural strength were  ascertained after 7 days and 28 days. Marble and ceramic  waste were utilized to partially replace sand and coarse  aggregate at different replacement levels, while maintaining  a constant water-cement ratio. The mix design M25 has  been designed in accordance with the IS 10262. The  compositions were identified as a combination of different  proportions of marble and ceramic waste, from 0%, 10%,  20% and 30%, to assess diverse characteristics.
Keywords: Marble Waste; Ceramic Waste; Coarse Aggregate; Rigid Pavement